Assessment of electrical conductivity and germinability of groundnut genotype seeds - Akuo, Ruth; Okiria, Latif Aisu; Ssemugenze, Brian; Gumisiriya, Costa; Kabaale, Fred Peter; Ocwa, Akasairi (Acta Agraria Debreceniensis, 2025)
Seed quality affects crop establishment and productivity. In addition, the use of good-quality seed is an essential prerequisite for sustainable crop production including groundnuts. Assessing germinability and electrical conductivity provides early evidence of the production potential of a given crop variety or genotype. Therefore, this study assessed the germinability and electrical conductivity of seeds of three groundnut genotypes. A laboratory experiment arranged in a Completely Randomized Design (CRD), replicated three times, was conducted at the Faculty of Agriculture, Kyambogo University, in 2020. Seeds of Igola, Serenut 1, and Serenut 2 groundnut varieties were tested, and data was collected on germination percentage and electrical conductivity. Analysis of variance (ANOVA) was performed using GenStat and means were separated using the least significant difference test at a 5% probability level. Germination percentage and electrical conductivity significantly (p